2006
DOI: 10.1007/s11270-006-9178-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of White Lupin Plant for Phytostabilization of Cd and As Polluted Acid Soil

Abstract: Cadmium and arsenic are two of the most important and toxic pollutants ubiquitous in the environment. The occurrence of numerous polluted areas as the affected by the accident of Aznalcóllar pyrite mine has promoted the employment of the phytoremediation as a feasible technology able to control and reduce the risk of this contamination at low cost. White lupin plant is proposed as a candidate for phytoremediation. This work aims to study if it is possible to use white lupin in phytoremediation of soils affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(50 citation statements)
references
References 26 publications
4
39
0
2
Order By: Relevance
“…Overall, the results support the hypothesis that L. uncinatus could be used in the combined strategies to recover Zn-and Cd-contaminated soils. The use of L. uncinatus could associate the advantages of using leguminous plants and the efficiency in phytostabilization (Ehsan et al 2009) as also demonstrated for other trace elements in the case of white lupin (Vazquez et al 2006;Esteban et al 2008) and also in case of other plants such as Viguiera dentata, Parthenium bipinnatifidum, Flaveria angustifolia, F. trinervia, and Sporobolus indicus which could be used to vegetate soils with large amounts of As, Cu, Pb, and Zn (Franco-Hernández et al 2010). Its efficiency in accumulating Cd in the roots, with very low translocation rate to the shoots, could make it a good choice in phytostabilization, preventing leaking of Cd from contaminated soils.…”
Section: Zn and CD Distribution In Various Plant Partsmentioning
confidence: 95%
See 1 more Smart Citation
“…Overall, the results support the hypothesis that L. uncinatus could be used in the combined strategies to recover Zn-and Cd-contaminated soils. The use of L. uncinatus could associate the advantages of using leguminous plants and the efficiency in phytostabilization (Ehsan et al 2009) as also demonstrated for other trace elements in the case of white lupin (Vazquez et al 2006;Esteban et al 2008) and also in case of other plants such as Viguiera dentata, Parthenium bipinnatifidum, Flaveria angustifolia, F. trinervia, and Sporobolus indicus which could be used to vegetate soils with large amounts of As, Cu, Pb, and Zn (Franco-Hernández et al 2010). Its efficiency in accumulating Cd in the roots, with very low translocation rate to the shoots, could make it a good choice in phytostabilization, preventing leaking of Cd from contaminated soils.…”
Section: Zn and CD Distribution In Various Plant Partsmentioning
confidence: 95%
“…Some Lupinus species are able to accumulate Zn (Pastor et al 2003), Cd (Brennan and Bolland 2003), Mg and Al (Reay and Waugh 1981), Hg (Vera et al 2002;Esteban et al 2008), and Pb and Cr (Ximenez-Embun et al 2001). Moreover, white lupin (Lupinus albus L.) tolerance to Cd and As with few toxic visual symptoms has been reported (Zornoza et al 2002;Vazquez et al 2005), as well as its ability for phosphateassisted phytoextraction of As (Tassi et al 2004) and for phytostabilization of acidified multi-contaminated soils (Vazquez et al 2006). Ximenez-Embun et al (2001) reported that L. albus, L. luteus, L. angustifolius, and L. hispanicus were able to grow under extreme conditions (wastewater, pH lower than 2) and to remove 98 % of the initial amount of toxic metals present in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…found that E. cladocalyx had the highest biomass and did not to affect As availability making it a good candidate for phytostabilization of As in gold mine tailings. In an earlier study, Vazquez et al (2006) reported that white lupin reduced Cd and As solubility in the soil while it accumulated significant amounts of the metals in its roots and nodules.…”
Section: Phytoremediationmentioning
confidence: 97%
“…Although generally, beans are sensitive to metals, some leguminous plants have the capacity to tolerate metals. Lupinus albus was found to be a good candidate for stabilizing As and Cd in soils (Vazquez et al, 2006). Several benefits in using this legume include improvement in soil properties due to atmospheric N fixations, increase in the pH of acidic soils, decrease in CaCl 2 -extractable As and Cd, and retention of these elements in the roots.…”
Section: Phytoremediationmentioning
confidence: 99%
“…The experimental plot has been described by Vázquez et al (2006), and has a wide range of pH (2e8), low contents of organic matter (<2%), nitrogen (<0.1) and carbonates (<0.1%) and a loamy-sandy texture.…”
Section: Field Experimentsmentioning
confidence: 99%